Hydrothermally reduced nano porous graphene–polyaniline nanofiber composites for supercapacitor - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (FlatChem, 2017)
Hydrothermally reduced porous graphene (PGs) and polyaniline (PANI) nanofiber composites (PGs?PANI) were prepared by interfacial polymerization of aniline in the presence of reduced porous graphene (PGs) under acidic conditions. Hydrothermal reduction of graphene oxide (GO) produced graphene quantum dots (GQDs) along with porous reduced graphene (PGs). The removal of nano sized GQDs generate several round shaped edges in the graphene, which facilitated improved charge storage. In addition to preparation of porous graphene, we developed an approach to process the PGs. We envisioned preparing conjugated polymer as processing material. The capacitive behavior of PGs was characterized using cyclic voltammetry (CV) and galvanostatic charge?discharge (GCD) techniques. The specific capacitance of hydrothermally reduced GO (PGs) and PGs?PANI composites was 185 F/g and 357 F/g at 0.1 A/g in 1 M H2SO4 electrolyte. The energy density of PGs?PANI composite was obtained 49.58 W h/kg at a power density of 71.8 W/kg.